A number theory problem by sudoku subbu

The sum of all positive integers n n for which the expression n 2 19 n + 99 n^2 - 19n + 99 is a perfect square is ?


The answer is 38.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Shubhendra Singh
Mar 16, 2015

n 2 19 n + 99 m 2 = 0 n^{2} -19n +99-m^{2}=0

Since n I n \in I so Discriminant D D of the above equation is a perfect squre

D = b 2 4 a c = 361 4 ( 99 m 2 ) = k 2 D=b^{2}-4ac=361-4(99-m^{2})=k^{2}

35 + 4 m 2 = k 2 \Rightarrow -35+4m^{2}=k^{2}

4 m 2 k 2 = 35 \Rightarrow 4m^{2}-k^{2}=35

By this m 2 m^{2} has only two integral values that are 81 , 9 81,9

Substitute these values in the given equation to get

n 2 19 n + 99 = 9 n^{2}-19n+99=9

n 2 19 n + 90 = 0 \Rightarrow n^{2}-19n+90=0

( n 9 ) ( n 10 ) = 0 \Rightarrow (n-9)(n-10)=0

A n d \Large And

n 2 19 n + 99 = 81 \Rightarrow n^{2}-19n+99=81

n 2 19 n + 18 = 0 \Rightarrow n^{2}-19n+18=0 ( n 1 ) ( n 18 ) = 0 \Rightarrow (n-1)(n-18)=0

By this n = 1 , 18 , 10 , 9 \large n=1,18,10,9

So the answer is 1 + 18 + 10 + 9 = 38 1+18+10+9=\huge38

Jessica Wang
Mar 24, 2015

Another approach is to complete the square:

n 2 19 n + 99 = x 2 n^{2}-19n+99=x^{2}

( n 19 2 ) 2 + 35 4 = x 2 \Rightarrow \left ( n-\frac{19}{2} \right )^{2}+\frac{35}{4}=x^{2}

4 ( n 19 2 ) 2 + 35 = 4 x 2 \Rightarrow 4\left ( n-\frac{19}{2} \right )^{2}+35=4x^{2}

( 2 n 19 ) 2 + 35 = ( 2 x ) 2 \Rightarrow \left ( 2n-19 \right )^{2}+35=\left ( 2x \right )^{2}

( 2 x ) 2 ( 2 n 19 ) 2 = 35 \Rightarrow \left ( 2x \right )^{2}-\left ( 2n-19 \right )^{2}=35

( 2 x 2 n + 19 ) ( 2 x + 2 n 19 ) = 35. \Rightarrow \left ( 2x-2n+19 \right )\left ( 2x+2n-19 \right )=35.

Therefore, ( 2 x 2 n + 19 , 2 x + 2 n 19 ) = ( 7 , 5 ) o r ( 35 , 1 ) . (2x-2n+19,2x+2n-19)=(7,5)\: or\: (35,1).

{ 2 x 2 n + 19 = 35 2 x + 2 n 19 = 1 \Rightarrow \left\{\begin{matrix} 2x-2n+19=35 & & \\2x+2n-19=1 & & \end{matrix}\right. and { 2 x 2 n + 19 = 7 2 x + 2 n 19 = 5 \left\{\begin{matrix} 2x-2n+19=7 & & \\ 2x+2n-19=5 & & \end{matrix}\right. .

We get x 1 = 9 , x 2 = 3 x_{1}=9,x_{2}=3 .

Substitute into n 2 19 n + 99 = x 2 n^{2}-19n+99=x^{2} , we have n = 1 , 9 , 10 , 18 n=1,9,10,18 .

Thus, the sum is 1 + 9 + 10 + 18 = 38 1+9+10+18=38

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...